In the shadows: a content analysis of the media’s portrayal of gender in far-right, far-left, and jihadist terrorists - Morgan, Skyler J. (Deviant behavior, 2021)
Women are underrepresented in the mass media and are most frequently portrayed in stereotypical and limited ways. Recent efforts to expand our understanding of the media’s representation of gender have examined the characterization of women in crimes stories as both victim and offenders. One avenue of this research focuses on the portrayal of women involved in terrorism. Although this body of research is limited and has been strictly qualitative, it has provided a useful framework for the current study. The current study sought to expand prior research on the media’s representation of gender and crime by systematically testing the six frames identified by Brigitte Nacos. As argued by Nacos, these six frames are used by the media to explain women’s involvement in terrorism. Using the United States Extremist Crime Data Base (ECDB), this study analyzed the news media articles that covered male and female perpetrators between the years of 1990 and 2016 from far-right, animal/environmental rights and jihadist movements. Findings indicated limited support for the original frames identified by Nacos. However, significant differences were found in the terrorist for the sake of love frame, such that female perpetrators were more likely to be presented through this frame. The current study identified two new frames used by the media to discuss perpetrators of terrorism, which included the disregarded frame, and the overshadowed frame. Of new frames identified in the current study, the overshadowed frame had large statistically significant differences between male and female perpetrators.